On some mites (Acari: Prostigmata) from the Interior Highlands: descriptions of the male, immature stages, and female reproductive system of Pseudocheylus americanus (Ewing, 1909) and some new state records for Arkansas - Skvarla, Michael J.; Fisher, J. Ray; Dowling, Ashley P.g. (Zootaxa, 2013)
The male and immature stages of Pseudocheylus americanus (Ewing, 1909) (Pseudocheylidae) are described and illustrated for the first time and the female is re-illustrated. The description of Pseudobonzia reticulata (Heryford, 1965) (Cunaxidae) is modified to include the presence of dorsal setae f2, which were not reported in the original description. In addition, Bonzia yunkeri Smiley, 1992 and Parabonzia bdelliformis (Atyeo, 1958) (Cunaxidae) are reported from the Ozark Mountains, Caeculus cremnicolus Enns, 1958 (Caeculidae) is reported from the Ozark and Ouachita Mountains, and Dasythyreus hirsutus Atyeo, 1961 (Dasythyreidae) is reported from Missouri and the Ouachita Mountains in Arkansas.